Accelerated and motion‐robust in vivo T2 mapping from radially undersampled data using bloch‐simulation‐based iterative reconstruction. Issue 3 (17th April 2015) - Ben‐Eliezer, Noam; Sodickson, Daniel K.; Shepherd, Timothy; Wiggins, Graham C.; Block, Kai Tobias
Abstract : Purpose: Development of a quantitative transverse relaxation time (T2 )‐mapping platform that operates at clinically feasible timescales by employing advanced image reconstruction of radially undersampled multi spin‐echo (MSE) datasets. Methods: Data was acquired on phantom and in vivo at 3 Tesla using MSE protocols employing radial k‐space sampling trajectories. In order to overcome the nontrivial spin evolution associated with MSE protocols, a numerical signal model was precalculated based on Bloch simulations of the actual pulse‐sequence scheme used in the acquisition process. This signal model was subsequently incorporated into an iterative model‐based image reconstruction process, producing T2 and proton‐density maps. Results: T2 maps of phantom and in vivo brain were successfully constructed, closely matching values produced by a single spin‐echo reference scan. High‐resolution mapping was also performed for the spinal cord in vivo, differentiating the underlying gray/white matter morphology. Conclusion: The presented MSE data‐processing framework offers reliable mapping of T2 relaxation values in a ∼5‐minute timescale, free of user‐ and scanner‐dependent variations. The use of radial k‐space sampling provides further advantages in the form of high immunity to irregular physiological motion, as well as enhanced spatial resolutions, owing to its inherent ability to perform alias‐free limited field‐of‐view imaging. Magn Reson Med 75:1346–1354, 2016. © 2015 Wiley Periodicals, Inc.